2005
DOI: 10.1002/pmic.200401002
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression patterns in zebrafish skeletal muscle: initial characterization and the effects of hypoxic exposure

Abstract: Patterns of protein expression were examined in white skeletal muscle from adult zebrafish (Danio rerio). High resolution two-dimensional gel electrophoresis resolved between 300 and 400 spots with molecular masses between 20 and 120 kDa and isoelectric points between about 5 and 8. Forty spots, representing a range of protein size, charge, and abundance were excised, digested with trypsin, and subjected to matrix-assisted laser-desorption/ionisation-time of flight mass spectrometry for protein identification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 49 publications
3
47
0
Order By: Relevance
“…From the MALDI-TOF mass spectra obtained from these four spots, we identified the M2 and M3 CK isoforms. However, additional CK spots covering a mass range of 10-30 kDa were also identified across the charge dimension, a finding consistent with the skeletal muscle proteome of zebrafish [20].…”
Section: Identification Of Common Carp Skeletal Muscle Proteinssupporting
confidence: 72%
See 1 more Smart Citation
“…From the MALDI-TOF mass spectra obtained from these four spots, we identified the M2 and M3 CK isoforms. However, additional CK spots covering a mass range of 10-30 kDa were also identified across the charge dimension, a finding consistent with the skeletal muscle proteome of zebrafish [20].…”
Section: Identification Of Common Carp Skeletal Muscle Proteinssupporting
confidence: 72%
“…The muscle samples were also analysed by 2-DE, immediately following homogenisation. Bosworth et al [20] observed Figure 6. Peptide coverage maps for the isoforms of CK isoforms and fragments.…”
Section: Ck Isoform Mappingmentioning
confidence: 96%
“…While these results point to an important role of GST during hypoxia, given the design of the experiment, it is not clear whether aerial exposure or subsequent re-immersion (re-oxygenation) caused the increase in antioxidant proteins. Studies on hypoxia-induced proteins in brain tissue of male medaka (Oryzias latipes) also showed an increase in GST (Oehlers et al, 2007), but brain and skeletal muscle in carp (Carasssius carassius) and zebrafish (Danio rerio), respectively, did not identify GST among proteins changing in response to anoxia/hypoxia (Bosworth et al, 2005;Smith et al, 2009). …”
Section: Hypoxia-induced Antioxidant Responsementioning
confidence: 99%
“…In all three studies, hypoxia resulted in changes in the levels of numerous transcripts encoding proteins involved carbohydrate metabolism, protein synthesis, cell proliferation, and motility. In contrast, a proteomic study of zebrafish skeletal muscle revealed limited changes in protein expression after hypoxia (Bosworth et al, 2005). The difference between results of microarray and proteomic studies may be due to experimental design (levels and lengths of hypoxia) or biological differences (species, tissues, or developmental stages), or could be the result of uncoupling of mRNA and protein expression under hypoxia.…”
Section: Responses To Hypoxiamentioning
confidence: 89%